FTO‐mediated m6A demethylation regulates IGFBP3 expression and AKT activation through IMP3‐dependent P‐body re‐localisation in lung cancer - Haiyang Wang; Hui Peng; Zhenzhen Zhang; Yilimunuer Abulimiti; Jiayi Hu; Yongxin Zhou; Ping Ji; Dong Li (Clinical and Translational Medicine, 2025)
Abstract Lung cancer remains one of the leading causes of cancer‐related deaths worldwide, and a growing body of evidence suggests that RNA modifications, including methylation, play a critical role in its progression. In this study, we investigated the role of the RNA demethylase fat mass and obesity‐associated protein (FTO) in lung cancer progression and determined the underlying molecular mechanisms. FTO expression was significantly upregulated in LUAD and correlated with poor prognosis. FTO knockdown in lung patient‐derived organoids and LUAD cell lines reduced their proliferation, invasion, and migration, and FTO knockdown in a KrasG12D mouse model reduced the growth of lung tumours. Mechanistically, FTO demethylated m6A sites in the insulin‐like growth factor‐binding protein 3 (IGFBP3) 3′UTR, preventing IMP3 binding. The ribonuclear protein IMP3 was identified as a crucial functional reader that interacted with m6A‐modified sites in the IGFBP3 3′UTR, thereby promoting IGFBP3 mRNA localisation to P‐bodies and suppressing its translation. Elevated IGFBP3 activated AKT signalling and promoted tumour progression. Collectively, we revealed that FTO drives lung cancer progression via m6A‐dependent sequestration of IGFBP3 mRNA into P‐bodies by IMP3, which suppresses translation and activates AKT signalling. The FTO–IGFBP3–AKT axis thus represents a promising therapeutic target. Key points FTO regulates the translation of IGFBP3 by demethylating m6A sites in the 3′‐untranslated region of IGFBP3 mRNA. Binding of the m6A reader protein IMP3 to 3′UTR m6A sites in IGFBP3 mRNA promoted its localisation and sequestration in cellular organelles known as to P‐bodies, thereby suppressing IGFBP3 mRNA translation. IGFBP3 regulates activation of the AKT signalling pathway, and that FTO‐mediated regulation of IGFBP3 influences LUAD malignant behaviours.